Land use and climate change interaction triggers contrasting trajectories of biological invasion - Syed Amir Manzoor (Elsevier, 2021)
Global change drivers such as land use and climate changes are known to interact in their effects on biodiversity. The impact of these drivers on global biodiversity is increasingly evident in many forms including the spread of invasive species. Climate and land use changes affect introduction, colonization and spread of invasive species by affecting niche availability and dispersal potential. We tested the combined effects of land use and climate changes on the current and future habitat suitability of Rhododendron ponticum in Wales using a MaxEnt-based ecological niche model. We used two policy-driven land use change projections for Wales, in combination with two General Circulation Models and two Representative Concentration Pathways to derive eight different land use and climate change scenarios. In seven out of eight scenarios, the habitat suitability for R. ponticum is likely to reduce by 2030. However, in the eighth scenario representing an extreme where land use change and greenhouse gas emissions both accelerate, the interaction of land use and climate change forces an increase of habitat suitability of R. ponticum. The study highlights the importance of considering the combined effect of land use and climate change and including regional policy-based land use change projections to test the potential of an invasive species to expand or retreat in future.